The Global Reciprocal Reprogramming between Mycobacteriophage SWU1 and Mycobacterium Reveals the Molecular Strategy of Subversion and Promotion of Phage Infection - Fan, Xiangyu; Duan, Xiangke; Tong, Yan; Huang, Qinqin; Zhou, Mingliang; Wang, Huan; Zeng, Lanying; Young, Ry F.; Xie, Jianping (Frontiers in Microbiology, 2016)
Bacteriophages are the viruses of bacteria, which have contributed extensively to our understanding of life and modern biology. The phage-mediated bacterial growth inhibition represents immense untapped source for novel antimicrobials. Insights into the interaction between mycobacteriophage and Mycobacterium host will inform better utilizing of mycobacteriophage. In this study, RNA sequencing technology (RNA-seq) was used to explore the global response of Mycobacterium smegmatis mc2 155 at an early phase of infection with mycobacteriophage SWU1, key host metabolic processes of M. smegmatis mc2 155 shut off by SWU1, and the responsible phage proteins. The results of RNA-seq were confirmed by Real-time PCR and functional assay. 1174 genes of M. smegmatis mc2 155 (16.9% of the entire encoding capacity) were differentially regulated by phage infection. These genes belong to six functional categories: (i) signal transduction, (ii) cell energetics, (iii) cell wall biosynthesis, (iv) DNA, RNA, and protein biosynthesis, (v) iron uptake, (vi) central metabolism. The transcription patterns of phage SWU1 were also characterized. This study provided the first global glimpse of the reciprocal reprogramming between the mycobacteriophage and Mycobacterium host.